ANALISIS ASUHAN KEPERAWATAN DALAM PEMBERIAN PRENATAL YOGA DENGAN AROMATERAPI TERHADAP KUALITAS TIDUR IBU HAMIL TRIMESTER III - Kiki Audilah (2022)
Pregnancy is a process of fertilization between an egg cell and a sperm cell so that a fetus is formed and undergoes physiological and psychological changes that occur in prospective mothers for 9 months. Physiological and psychological changes experienced by pregnant women such as breast enlargement, weight gain, increased frequency of urination, back pain, disturbances in sleep patterns and sleep quality that occur in pregnant women. To overcome this problem, especially the problem of sleep quality in pregnant women, it can be overcome by non-pharmacological therapy, namely prenatal yoga with aromatherapy. Prenatal yoga has good movements for pregnant women that can practice breathing, improve body position, and improve sleep quality for pregnant women in the third trimester. The purpose of the study was to determine the effectiveness in the application of prenatal yoga with arotherapy in performing nursing care. This study uses the literature review method with the application of evidence based nursing in nursing care for two patients with sleep quality problems that occur in third trimester pregnant women. The instrument used to measure sleep quality is the Pittsburgh Sleep Quality Index (PSQI). The results obtained after being given prenatal yoga with aromatherapy with a score of 5 out of a score of 15.